PENGARUH TEMPERATUR INKUBASI DAN JENIS RAGI DALAM PEMBUATAN BIOETANOL DARI LIMBAH KULIT PISANG (Musa Paradisiaca) - Febriana, Ida (KINETIKA, 2018)
As we know, the current energy demand is not proportional to the increasing availability of fuel thinning. Therefore we need a research to get alternative source of renewable energy by utilizing biomass waste like banana peel. In this study is to use banana skin waste in the industrial area of banana processing that has been taken the meat, and the skin is left to rot and become organic fertilizer. The purpose of this research is how the influence of incubation temperature and yeast type on variation of banana skin type to bioethanol content. The research method is by hydrolysis of starch, fermentation, and analysis of bioethanol yield using gas chromatography (GC-FID (Flame Ionization Detector)), shimadzu, Kyoto, 2010). Based on the result of the research, it can be seen that the sample of banana leaf waste (musa balbisiana) produce the most bioethanol with yeast bread type at incubation temperature 30ËšC that is 0,5854%, then banana kepok (paradisiaca L) and king banana leather ( musa sapientum) with each bioethanol content of 0.4587% and 0.4173%